A Mathematically Developed Dynamic Model for Laterally Loaded Piles - Bahrami, Amir; Nikraz, Hamid (Pile 2013 International Conference Undertaken by IRSM, 2013)
Baranov-Novak model is reassessed for its application in pile dynamic problems. Argument is made on the physical meaning of real and imaginary parts of the mathematical solution. Frequency dependent stiffness and damping are investigated. Contribution of the soil inertia in pile lateral vibration is interpreted as a distributed mass over the length of the pile. A simple dynamic model for the soil-pile-structure interaction is proposed as a generalized beam on Winkler foundation including lateral springs, dampers and masses.